Antioxidant Activity Testing of Fractions Resulting from Gravity Column Chromatography of Methanol Extract of Kepundung Leaves (Baccaurea racemosa) Using The DPPH Method - Istiqamah, Juhratul; Permatasari, Lina; Hanifa, Nisa Isneni (Jurnal Biologi Tropis, 2024)
Free radicals are compounds that can cause various diseases and can be inhibited with antioxidant compounds. One of the antioxidant compounds that can be obtained from natural sources is the kepundung plant (Baccaurea racemosa). This research aims to determine the fraction that contains flavonoid compounds and determine the percent inhibition of the fraction resulting from gravity column chromatography from the methanol extract of kepundung leaves (Baccaurea racemosa) using the DPPH method. Extraction used the sonication method and continued with fractionation using gravity column chromatography. A UV-VIS spectrophotometer was then used to measure the antiradical activity and perform a qualitative flavonoid and antioxidant test using TLC. The study's findings demonstrated that the yield of a 96% methanol extract of kepundung leaves was 17%, and that there were 15 sets of fractions produced by gravity column chromatography. Positive results for flavonoids and antioxidants were shown by fractions B, G, H, K, L, and N. The fraction with the highest antiradical activity was fraction L with a % inhibition value of 79,94%.